Synthesis and Characterization of Poly-3, 4-ethylenedioxythiophene/2, 5-Dimercapto-1, 3, 4-thiadiazole (PEDOT-DMcT) Hybrids. (10th June 2015) - Rodríguez-Calero, Gabriel G.; Conte, Sean; Lowe, Michael A.; Gao, Jie; Kiya, Yasuyuki; Henderson, Jay C.; Abruña, Héctor D.
Graphical abstract: Abstract: Organosulfur Compounds (OSCs) represent an attractive alternative as organic cathode materials for electrochemical energy storage (EES) applications. They intrinsically have high gravimetric capacity (although low volumetric) and are typically inexpensive, since they are composed of abundant elements (i.e. C, N, O, and S). However, OSCs, specifically thiolate-containing OSCs generally suffer from slow charge transfer kinetics. To mitigate the charge transfer limitations, conducting polymers (CPs) such as poly-3, 4-ethylenedioxythiophene (PEDOT) have been employed as electrocatalysts. In this manuscript, we have covalently modified a PEDOT film with an OSC (i.e. 2, 5-dimercapto-1, 3, 4-thiadiazole di-lithium salt (Li2 DMcT)). We have developed a synthetic strategy that employs, for the first time, a post-polymerization modification reaction as a tractable and viable technique to modify organic materials for EES electrodes. Electrochemical characterization, via cyclic voltammetry showed the expected pseudocapacitive response of PEDOT with the superimposed faradaic processes of the covalently bound DMcT. Moreover, spectroscopic characterization using Raman spectroscopy provided mechanistic insights into the electrochemical reactions. Furthermore, we electropolymerized films onto coin-cell electrodes and tested them in half-cell configurations and found that the capacity retention of the films was significantly enhanced, when compared with the PEDOT/DMcT composites (mixed but not covalently bound).